Fungi present distinguishable isotopic signals in their lipids when grown on glycolytic versus tricarboxylic acid cycle intermediates - S. Jabinski; S. Jabinski; V. Kučera; V. Kučera; M. Kopáček; M. Kopáček; J. Jansa; T. B. Meador; T. B. Meador; T. B. Meador (Biogeosciences, 2025)
Microbial activity in soils controls both the size and turnover rates of large carbon (C) inventories stored in the subsurface, having important consequences for partitioning of C between terrestrial and atmospheric reservoirs as well as recycling of mineral nutrients such as nitrogen or phosphorus (often bound to the C) that support plant growth. Fungi are major decomposers of soil organic matter (SOM); however, uncertainty about the identity of predominant C substrates that fuel their respiration confound models of fungal production and SOM turnover. To further define the signals of microbial heterotrophic activity, we applied a dual hydrogen (H) and C stable isotope probing (SIP) approach to pure fungal cultures representing the phyla Ascomycota, Basidiomycota, and Zygomycota growing on monomeric (glucose, succinate) or complex substrates (tannic acid, β-cyclodextrin). Our findings demonstrate that the investigated species incorporated only minor quantities of inorganic C (provided as bicarbonate) into their membrane lipids, amounting to < 3 % of lipid-C, with no consistent patterns observed between species or growth substrates. The net incorporation of water-derived H (i.e., aw) into lipids also did not differ significantly between incubations with monomeric versus complex substrates; however, growth on succinate elicited significantly higher aw values than glucose or β-cyclodextrin. This finding suggests that 2H-SIP assays have the potential to distinguish between microbial communities supported predominantly by substrates that are catabolized by the tricarboxylic acid cycle versus glycolytic pathway. Furthermore, the average aw value of heterotrophic fungal incubations 0.69 ± 0.03 (SEM) is consistent with that observed for bacterial heterotrophs and may be applied for upscaling lipid-based estimates of fungal production in environmental assays.